PERSEPSI DAN FAKTOR-FAKTOR DETERMINAN KEPUTUSAN PEMBELIAN - Bita Sari Kusuma Arifiani; Aprih Santoso (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
The problem of this research is that from the predetermined targets not able to be achieved, theproblem shows the decline in purchasing decisions by consumers of PT. Transfarma SemarangBranch and this study aims to analyze the factors of consumer trust, consumer experience andsales promotion against the purchasing decisions of PT. Transfarma Semarang Branch. Thepopulation in this study were all consumers of PT. Transfarma Semarang Branch which amountedto 566 consumers while the sampling technique used was a non probability sampling techniquewith a type of purposive sampling and the analysis tool used in this study was multiple linearregression. The results showed that the variables of consumer confidence, consumer experienceand sales promotion had a positive and significant effect on the purchasing decisions of PT.Transfarma Semarang Branch and the results of the adjusted R square value in the regressionmodel were obtained at 0.584 which means that 58.4 percent of purchasing decision variables canbe explained by variables of consumer confidence, consumer experience and sales promotionwhile the remaining 41.6 percent is explained by other variables outside of this study.